Monitoring Kadar Amonia dalam Akuarium Ikan Menggunakan Metode Verifikasi Warna RGB dengan Memanfaatkan ESP32-CAM - Matius Bryant; Stephanus Antonius Ananda (Universitas Kristen Petra, 2022)
The main problem that is often found is poor aquarium water quality during the maintenance period, which can result in an increase of ammonia levels in the aquarium. In this thesis, the specimen that will be used for testing is predatory fish, where the food of this fish is raw meat or live fish whose size is smaller than them. The leftover of this food can increase the production of ammonia in the aquarium water. An increase in ammonia production will result in an increase in the nitrogen cycle as well, where the cycle will produce more nitrogen which results in reduced oxygen in the water. The effect of ammonia on fish can vary from difficulty of breathing, loss of appetite, and over time it will cause death in fish. In this thesis, an IoT(Internet of Things)- based monitoring system for aquarium ammonia levels will be used. This problem has actually been handled in several previous studies, one of which was researched by Talanta, D. E. entitled